Deni CITRA MEREK, KEPUASAN PELANGGAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN MS Glow Majalengka: LOYALITAS PELANGGAN MS Glow Majalengka - Deni Istiono; Pupung Pamungkas; Nining Kurniasih (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
ABSTRACT MS Glow is a local skincare brand in Indonesia that has successfully built a strong market position, including in Majalengka Regency. This research is motivated by MS Glow’s ability to maintain its presence in the beauty industry amid fluctuations and competition from other brands. Customer loyalty refers to a strong commitment from customers to continue purchasing and supporting preferred products in the future. Loyalty plays an important role in business sustainability because loyal customers tend to make repeat purchases and recommend products to others. The success of building customer loyalty is closely related to the roles of brand image, customer satisfaction, and trust. These three variables are considered important in shaping customer loyalty, as a positive brand image, high levels of customer satisfaction, and strong customer trust can encourage repeat purchases and recommendations to others. This study uses a quantitative method with a descriptive verificative approach. The research population consists of MS Glow customers in Majalengka Regency, whose exact number is unknown. A sample of 100 respondents was obtained using a non-probability sampling technique with an accidental sampling method. Data were collected through online questionnaires and analyzed using SPSS. The results show that brand image and customer satisfaction have a positive and significant effect on customer loyalty, while trust does not affect customer loyalty